Gasdermin D promotes AIM2 inflammasome activation and is required for host protection against Francisella novicida - Zhu, Qifan (J Immunol, 2018)
The DNA sensor absent in melanoma 2 (AIM2) forms inflammasome complex with ASC and caspase-1 in response to Francisella tularensis subsp. novicida (F. novicida) infection leading to maturation of IL-1β and IL-18 and pyroptosis. AIM2 is critical for host protection against F. novicida infection in vivo; however, the role of pyroptosis downstream of the AIM2 inflammasome is unknown. Recent studies have identified gasdermin D (GSDMD) as the molecule executing pyroptosis by forming pores on plasma membrane following activation by inflammatory caspase-1 and −11. In this study, we report that GSDMD-deficient mice were susceptible to F. novicida infection compared to wild type (WT) mice. Interestingly, we observed that GSDMD is required for optimal caspase-1 activation and pyroptotic cell death in F. novicida-infected bone marrow-derived macrophages (BMDMs). Furthermore, caspase-1 activation was compromised in BMDMs lacking GSDMD stimulated with other AIM2 inflammasome triggers including poly(dA:dT) transfection and mouse cytomegalovirus (MCMV) infection. Overall, our study highlights a previously unknown function for GSDMD in promoting caspase-1 activation by AIM2 inflammasome.